A sensitivity study of the factors affecting the risks associated with the disposal of spent nuclear fuel in a geological disposal facility in a clay environment. (October 2021) - Marsh, Ashley I.; Williams, Laurence G.; Lawrence, James A.
Abstract: The disposal route for the UK's inventory of spent nuclear fuel has yet to be decided upon, however if the UK follows the approach taken by many nations, its spent nuclear fuel will be destined for geological disposal. This paper provides a simplified, approach to the calculation of radiological risk posed to members of the public, associated with the disposal of spent advanced gas-cooled reactor (AGR) nuclear fuel in a geological disposal facility (GDF) located in a hypothetical clay geological setting. Simulating the release of radionuclides at differing levels of complexity shall aid in the development of aspects of the design, construction, operation, decommissioning and post-closure phases of geological disposal and the development of a safety case for geological disposal. This paper presents a high-level, 1-D model built in GoldSim, to provide an initial indication of the radiological risks to the public, the nature of which would require further development into a complex total system model in order to facilitate risk evaluation supplementary to a safety case. The model was validated against benchmark calculations provided by Radioactive Waste Management Ltd. The base case calculations suggest that the predicted risks to the potential exposed groups are well below, approximately 2 orders, the recommended risk guidance level of 1 × 10 −6 per year. A number of sensitivity studies were carried out to identify the importance of various factors that could influence the predicted risks. Sensitivity analysis indicated that the most influential sensitivities on the annual risk posed by geological disposal were the depth and rate at which spent nuclear fuel dissolved in contact with groundwater. The pathways available for groundwater flow to the biosphere were also noted to significantly alter the peak risk observed; crucially almost all sensitivities did not increase the peak risk to within 1 order of magnitude below the recommended risk guidance level. Validation for a second hypothetical high strength rock geological setting resulted in higher projected predicted risks to the potential exposed groups although risk levels remained below the recommended risk guidance level. This suggests a clay environment may have favourable characteristics for the final disposal of spent nuclear fuel compared to a high strength rock alternative. Graphical abstract: Image 1 Highlights: Spent nuclear fuel, including AGR fuel, may yet be disposed of in the UK's GDF. We present a simple model of radionuclide release from AGR fuel in a GDF in clay. The annual radiological risk to potentially exposed groups were predicted. Sensitivities were simulated to observe the impact of variables on peak risk. Results indicate peak risk remains two levels below recommended guidance level.